PENGEMBANGAN BAHAN AJAR BERBASIS STAD DIPADU INKUIRI TERBIMBING PADA MATERI HOMOLOGI - Siti Nurhidayati; Khaeruman Khaeruman (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT: The available teaching materials, especially on the homology materials are still limited to the knowledge, not yet emphasized on the process, so some students become passive, and this certainly influences the learning outcomes. Homology deals with organs that have different structures, but they have the same function. This is very much happening around us, for it is very necessary to be discussed and demonstrated so as to maximize student activity. One of the solutions offered is the development of STAD-based teaching materials combined with guided inquiry. Through STAD students can discuss various matters related to homology in the surrounding environment, while through guided inquiry students can demonstrate homology, and certainly better understand the process from formulating the problem, formulating goals, formulating hypotheses, determining data collection, taking data, analyzing up to conclusion. This will certainly improve the mentality and self-confidence of the students. The purpose of this study is to develop STAD-based teaching materials combined inquiry on guided homology material. The type of this research is Research Development using model design of Dick & Carey and Paulina & Purwanto in Paizah (2011). The instrument used in the form of a questionnaire is then analyzed descriptively. The developed teaching materials contain; pre-introduction, introduction, summary, evaluation, and closing. Expert content validation results about 80% content presentation and 85% content presentation with good category, while material expert validation about material feasibility is 90% and material presentation is 87% with very good category. Individual test result of 88,17% with very good category. For that it is concluded that; The development of teaching materials with STAD method combined with guided inquiry on homology material is suitable for use.